Does the Life Course Timing of a Label Matter? The Impact of Mental Health Labels on Crime in Adulthood - Wilkinson, Lindsey (Journal of developmental and life-course criminology, 2023)
Despite dramatic increases in the labeling of mental health disorders in children and young adults—disorders such as attention-deficit/hyperactivity disorder (ADHD), depression, and anxiety—insufficient attention has been paid to the effects of these mental health disorders and their diagnostic labels, on crime across the life course. Labeling theory suggests that a mental health diagnosis itself (the label) causes crime by creating negative self-appraisals and withdrawal from conventional networks important to the development of prosocial bonds. Other theoretical models, including self-control theory and strain theory, suggest that mental health symptoms instead cause crime by weakening internal controls and/or creating negative affect that is resolved through criminal behavior. The research in this paper seeks to address these theoretical arguments by asking whether childhood, adolescent, and adult mental health symptoms and mental health labeling affect adult self-reported criminal behavior. Using data from the National Longitudinal Study of Adolescent to Adult Health (N = 11,197), this study examines how a mental health diagnosis (label) affects subsequent crime after controlling for symptoms of anxiety, ADHD, and depression and the life course stage in which labels are given. Our results indicate that mental health labels, especially a depression label in adolescence, increase self-reported crime, even after controlling for mental health symptoms and measures of strain and self-control theories. This research therefore suggests that mental health labeling and the life course timing of the labeling are important avenues to consider as interventions meant to prevent crime among young adults.